Optimalisasi Partisipasi Siswa melalui Pembelajaran Berbasis Diskusi: Studi Kasus di SMP Bilingual Terpadu Junwangi Krian Sidoarjo - Adi, Muhammad Iqbal Fikri; Rahmah, Nadia Wulida; Farhan, Farhan (EL-BANAT: Jurnal Pemikiran dan Pendidikan Islam, 2024)
This study examines the implementation of the Discussion-Based Learning Model in increasing the active participation of students at the Integrated Bilingual Junior High School, Junwangi Village, Krian Sidoarjo. This research aims to provide guidance for teachers in choosing an effective learning model, so that it makes it easier for students to understand the material being taught. The research method used is observation and interviews to collect data related to student activity. The observation results showed that students dared to express their opinions, enthusiastically answered questions or quizzes from teachers, and actively asked questions to teachers or fellow students when there was material that was poorly understood. In addition, students also participate in group discussions according to the teacher's direction. The implementation of this model shows that the discussion method is effective in increasing student participation and preparing teachers in managing discussions. Through the discussion model, students' interest in learning increases and the learning process becomes more creative